Dysmature patterns of newborn EEG recordings: Biological markers of transitory brain dysfunction or brain injury. (May 2022) - Rener-Primec, Zvonka; Neubauer, David; Osredkar, Damjan
Abstract: Perinatal hypoxic-ischemic brain injury is a major cause of non-progressive neurological deficits in children. Dysmature patterns can be seen in newborns' electroencephalograms (EEGs) and may have prognostic value for long-term outcomes. Objective: To investigate the prognostic value of dysmature EEG patterns in term or near-term newborns. Methods: Neonates with dysmature patterns in their first neonatal EEG, assessed during a 6-year period from January 2010 to December 2015, were included in the study. Their outcomes at their follow-ups in June 2019 (at the age of 3 years or more) were assessed, and the presence of neurological deficits and/or epilepsy was noted. Results: We identified 347 neonates with video-EEG recordings during the observed period, in which 10 neonates had dysmature patterns in their first EEG. Eight were born at term and two were born late preterms, born at the 35 and 36-week gestational age. The reasons for admission were HIE grade I in 2 patients, grade II in 6 neonates, and heart problems in 2 patients. The second EEG was recorded at different time intervals, in 7 infants between 1 and 6 weeks; three infants had second EEG much later and were excluded from the study. Six of seven infants showed normal background activity (BA), and five had sharp waves over different regions, all six had normal developmental outcomes. One child with dysrhythmic pattern in the second EEG was diagnosed with genetic encephalopathy, developed spastic cerebral palsy and died due to severe pneumonia at the age of 6 years. Conclusion: Dysmature patterns may reflect transitory brain dysfunctions. Neonatal EEG tests remain reliable and important diagnostic tool in the very first weeks of life, particularly due to the availability of sequential EEG recordings and interpretations. Highlights: Dysmature patterns may reflect transitory brain dysfunctions. EEG remains important diagnostic and prognostic tool in the very first weeks of life. Dysmature patterns of a neonatal EEG may have prognostic value.